PENGEMBANGAN MODEL KONSTRUKSI RUMAH PASCA BENCANA BERBASIS KEMAMPUAN LOKAL - Larasati, Dewi; Solihah, Kiki Zakiyatus (TERAS)
Post disaster housing reconstruction progress in Indonesia is still evaluated tardy and unsatisfied. The urgent need of a large amount of houses in a short time, the planning and execution of post-disaster housing reconstruction in Indonesia proceeded abruptly, without involved the community to participate in each phase. Mass house production system, whom contractor (3rd party) in Aceh post-disaster reconstruction had conducted (contractor-driven approach), did not satisfy most of the occupants because of its unfitness to the local character. It also generated the vacant house phenomena in some areas. Meanwhile, the reconstruction with community involvement, or called participatory approach, in Yogyakarta and Pangandaran (West Java) showed higher level of satisfaction. This matter also demonstrated by the research of post-disaster reconstruction in Gujarat, India. With the reliance to build their own houses, the occupants showed high sense of belonging. As a proof, the occupants even already stayed in the houses that had not been 100 % built. However, the conventional method and lack ness ability of unskilled labor in the reconstruction with community involvement caused the low productivity, inefficiency, and substandard of quality. However, this research aim to propose the model of post disaster house construction process based on local indigenous, which could be implemented in post disaster reconstruction process in Indonesia, with better quality, productivity and efficiency.